WATER CONING IN ASMARY RESERVOIR-FAUQI FIELD (Journal of Engineering, 2009)
Water coning in oil wells is one of the most serious problem because when the water reach to perforated zone, it will be produced with oil. Water with oil will form other problems in refinery, such as corrosion, and it will affect the purity of different petroleum products.The present work deals with fauqi field Asmari reservoir which is an active water drive reservoir.An empirical equation has been proposed to calculate the critical production rate. This equation is obtained by regression of the data which are collected from Missan oil field. The proposed equation gives better results than Schools and Myer equations when compared with the actual production rate.